The effects of particle breakage and shape on the strength parameters of sandy soil - D., Youventharan; Rokiah, O.; Mohd Arif, S. (IOP Publishing, 2021)
Many laboratory and full-scale studies found that pile foundation is a reliable structure that has a long-term durability. This aspect makes it favourable when construction is in an area like the coastal where granular materials are normally in great scale. Generally, method used for the installation of pilling such as the drop hammer method will involve high energy to drive a single pile into the ground. Hence, the soil particles may undergo serious physical changes that will affect the engineering properties of soil used in the design work. The main aim of this research is to know the impact of pile installation work on sand particles. To understand the impact of sand particle breakage to the soil strength, an actual soil breaking mechanism simulated in the laboratory by using an automated soil compactor where the sand samples were crushed using 500 and 1000 times of blows respectively. The behaviour of sand were then analysed using a series of test which are; sieve analysis, specific gravity, relative density and the shear box test in order to measure the engineering properties of the sand. Mackintosh probe test was conducted in-situ to identify the undrained shear strength of sand and to correlate the cohesion of the sand with laboratory testing. This research confirmed that particle breakage has a significant influence with sand shape and therefore its strength changes with crushing impact.